2021
DOI: 10.16926/par.2021.09.10
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of scoring, ingenuity of striking, art of flying — conceptual and systematical identification of soccer scoring techniques

Abstract: The terms of soccer scoring techniques (SSTs) used in practice and research have been remaining confusing; even dramatic, we still do not know how many SSTs available for the game. This scenario hinders not only the scientific studies on some unique SSTs but also the development of novel coaching methods for learning these SSTs. The current paper aims to bridge the gap by establishing a SST terminology system. The system is built based on goal repeatability, selected anatomical & biomechanical parameters, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…The 3D motion capture and biomechanical modeling were used to quantify striking power and accuracy [ 24 ]. The use of motion-capture permits allowed considerable freedom of movement without influencing the accuracy of data [ 32 , 33 , 34 , 35 ], so no restrictions were placed on the movement of the subject within the capture volume and subjects could perform without having to alter their normal body control. Using the manufacturer’s specified guidelines, calibration resolution yielded results that were accurate within 1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…The 3D motion capture and biomechanical modeling were used to quantify striking power and accuracy [ 24 ]. The use of motion-capture permits allowed considerable freedom of movement without influencing the accuracy of data [ 32 , 33 , 34 , 35 ], so no restrictions were placed on the movement of the subject within the capture volume and subjects could perform without having to alter their normal body control. Using the manufacturer’s specified guidelines, calibration resolution yielded results that were accurate within 1 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Obviously, relying on the aptness of the athletes to improve these virtuosic SSTs can hardly be considered a viable learning or coaching strategy. Worst of all, the terms surrounding SSTs used in practice and research have been confusing [ 10 ]; researchers and practitioners are not sure how many SSTs are available for the game. This scenario hinders not only the scientific studies on many exceptional SSTs but also the development of novel coaching methods for learning these SSTs.…”
Section: Introductionmentioning
confidence: 99%
“…Through systematic identification, a recent study [ 10 ] has revealed that there are 43 SSTs that exist in current soccer games. Surprisingly, there are only a handful of SSTs documented in the existing training/coaching literature and, consequently, the comprehensive list of SST training is presently limited to maximal instep kick (including the curled kick), jumping headers, and volley/side volleys [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations